Pojav in širjenje tujerodne vrste dnevnega metulja - pelargonijevega bakrenčka (Cacyreus marshalli (Butler 1898)) v Sloveniji - Verovnik, Rudi (Acta entomologica slovenica (Ljubljana), 2011)
Geranium Bronze (Cacyreus marshalli) is the first invasive butterfly species recorded in Slovenia. It was first observed in Gorjansko village on the Kras Plateau in autumn 2008. Next year an expansion followed with observations frommore than 30 sites in SW Slovenia. It was observed in Vipava valley, Kras Plateau, and in towns along the coastline. Although it was less frequent in 2010, it still managed to occupy some new sites, markedly the town Škofja Lokain central Slovenia. The larvae of Geranium Bronze feed on flower buds, stems and leaves of Pelargonium plants, and can cause severe damage. Due to late appearance of larger densities of adults, mostly not before September, the damage on the Pelargonium plants in Slovenia is still limited, but first signs of the presence of the species can be already observed in the coastal towns. As the species at present does not have an effective natural enemy it seems that cold winters are the limiting factor in abundance and expansion of the species in Slovenia. It is important to keep on monitoring the expansion of the Geranium Bronze as it could, apart from economic reasons, switch to autochthonous larval food plants and affect the survival of some autochthonousbutterfly and moth species.
Keywords: butterfly; distribution; entomologija; entomology; invasive species; invazivne vrste; Lepidoptera; metulji; pelargonije; Pelargonium; razširjenost